The Hundred islands (Taguig City, Philippines : Department of Science and Technology, 2011)
This book tells the story of technology enhancing businesses.
Food Processing -- Horticulture -- Marine and Aquatic -- GHD -- Furniture -- Metals and Engineering.
Keywords: BUSINESS